Direito fundamental à educação : pessoas com deficiência e a educação inclusiva - Xerez, Rogério Saraiva (2015)
In Brazil, the right to education is an integral of fundamental rights with express provision in the Federal Constitution of 1988 (CF / 88), in its Art.6 where this instance is seen as a universal right and wrote side by side to guarantees as to health, food, work, among others. Ensuring a basic right such as the education is a duty to the state and requires its implementation as a subjective right of every one, in particular people with disabilities who represents 24% of the Brazilian population. Thus, one can not forget that access to education so as not to respect the needs and limitations of the disabled person would be put into question its quality as a subject of law, disregarding their status as human beings. In this sense, the present work is an investigative work of theoretical nature that analyses the right to inclusive education of disabled people supported in the 1988 Federal Constitution and its principles of dignity, equality and social inclusion, and the infra laws.